f(x)=(x-1)(x-2)(x-3).(x-99)(x-100)求f(1)的导数
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 02:48:52
f(x)=(x-1)(x-2)(x-3).(x-99)(x-100)求f(1)的导数f(x)=(x-1)(x-2)(x-3).(x-99)(x-100)求f(1)的导数f(x)=(x-1)(x-2)(
f(x)=(x-1)(x-2)(x-3).(x-99)(x-100)求f(1)的导数
f(x)=(x-1)(x-2)(x-3).(x-99)(x-100)求f(1)的导数
f(x)=(x-1)(x-2)(x-3).(x-99)(x-100)求f(1)的导数
f′(x)=(x-1)′[(x-2)(x-3)(x-4)……(x-100)]+(x-1)[(x-2)(x-3)(x-4)……(x-100)]′ f(x=1)=1×[(-1)(-2)(-3)……(-99)]+(1-1)[(x-2)(x-3)(x-4)……(x-100)]′ =-99!
已知f(x)满足2f(x)+f(1/x)=3x,求f(x)
F(X)满足F(x)+2f(x分之1)=3X,求f(x)
已知f(x)满足2f(x)+f(1/x)=3x,求f(x)?
已知f(x)满足2f(x)+f(-x)=-3x+1,求f(x)
已知f(x)满足f(x)+2f(1/x)=3x,求f(x) ,
f(x-1)=x^2-2x+3(x
f(x)=(x-1)(x-2).(x-3)求导
f(x)=5x+3 f(x)=5x f(x)=x+2x+1 f(x)=5x+3 f(x)=5x f(x)=x+2x+1
已知函数f(x)=x^3+x^2-2x-x,f(1)f(2)
设f(x)={3x-1,x=0,求f(-x),f(x-2).
f(x+1)+f(x-1)=4x^3-2x求f(x)
已知f(x+1/x-1)=3f(x)-2x,求f(x)
已知f(x)+2f(1/x)=x+2/x+3,求f(x)
F(x)=3x^2+2x-1 求F(x+△x)-f(x)/ △x
f(x)+2f(1/x)=3x
f(1+x)+2f(1-x)=3x^2 求f(x)f(1+x)+2f(1-x)=3x^2求f(x)
f(x)={2x+1,x
f(x)={1+x/2,x